Synthesis and Application of Carbonated Fatty Acid Esters from Carbon Dioxide Including a Life Cycle Analysis. Issue 4 (11th March 2014) - Schäffner, Benjamin; Blug, Matthias; Kruse, Daniela; Polyakov, Mykola; Köckritz, Angela; Martin, Andreas; Rajagopalan, Prasanna; Bentrup, Ursula; Brückner, Angelika; Jung, Sebastian; Agar, David; Rüngeler, Bettina; et al.
Abstract Carbon dioxide can be used in various ways as a cheap C1 source. However, the utilization of CO2 requires energy or energy‐rich reagents, which leads to further emissions, and therefore, diminishes the CO2‐saving potential. Therefore, life cycle assessment (LCA) is required for each process that uses CO2 to provide valid data for CO2 savings. Carbon dioxide can be incorporated into epoxidized fatty acid esters to provide the corresponding carbonates. A robust catalytic process was developed based on simple halide salts in combination with a phase‐transfer catalyst. The CO2‐saving potential was determined by comparing the carbonates as a plasticizer with an established phthalate‐based plasticizer. Although CO2 savings of up to 80 % were achieved, most of the savings arose from indirect effects and not from CO2 utilization. Furthermore, other categories have been analyzed in the LCA. The use of biobased material has a variety of impacts on categories such as eutrophication and marine toxicity. Therefore, the benefits of biobased materials have to be evaluated carefully for each case. Finally, interesting properties as plasticizers were obtained with the carbonates. The volatility and water extraction could be improved relative to the epoxidized system.